Comparison between endocytosis and intracanalicular sequestration of cell-surface antigens in human platelets - Jennings, Brent (Division of Medical Biochemistry and Structural Biology, 2017)
Human platelets respond to various macromolecules in the plasma. Uptake of specific ligands, and antibodies to various epitopes on the platelet plasma membrane, has been observed. The platelet canalicular system has been shown to be involved with this uptake. Recently, investigators have speculated on the role of endocytosis in platelets to account for the presence of plasma proteins such as fibrinogen and immunoglobulin within platelet organelles. Antibodies binding to cell-surface antigens on platelets can lead to a redistribution of these antigens. When antibodies, specific for platelet cell-surface receptors, bind to platelets they may either undergo endocytosis into intracellular vacuoles, or may merely become sequestered within the canalicular system of platelets. The present study investigated whether endocytosis occurs in platelets. Such a process would lead to the endocytic uptake of a fluid-phase marker and would involve internalization and recycling of cell surface membrane. A fluid-phase marker (FITC-dextran) was used to measure any constitutive endocytic activity. In addition, a suitable membrane marker was used to determine whether membrane internalization occurred. This involved a technique whereby radioactive galactose was covalently attached to cell-surface glycoconjugates. A monoclonal antibody to the platelet receptor, GPIIbIIIa, was used in conjunction with the membrane marker in order to determine if membrane internalization was involved during the subsequent redistribution of the receptor-antibody complex. Immunocytochemical techniques using electron-dense probes were employed to localise the sites to which this receptor-antibody complex became redistributed. In comparison with reported rates of endocytic uptake of fluid-phase marker in other cell types, no significant endocytic activity could be detected with platelets, after taking their relatively small volume into account. Similarly, membrane internalization was not detected with resting platelets. Following challenge of the platelets with anti-GPIIbIIIa antibody, no membrane internalization could be measured during redistribution of the receptor-antibody complex. The compartment to which the receptor-antibody complex was redistributed could be identified morphologically as the canalicular system. The present data provide evidence for a process of sequestration of receptor-antibody in the canalicular system of resting platelets. It remains possible that other mechanisms exist within the platelet system for uptake of extracellular material as this study dealt exclusively with the platelet response to a specific antibody. These results may have implications with respect to the interaction of platelets with anti-platelet antibodies in the normal state, as well as with clinical disorders involving elevated levels of platelet-associated IgG. As far as can be deduced from the available literature, these data represent the first use of a covalent membrane marker in conjunction with uptake of macromolecules to study endocytic events in human platelets.